Faktor penyebab rendahnya hasil belajar matematika siswa dan implikasinya terhadap layanan bimbingan dan konseling di SMPN 12 Padang - Alfarisyi, Muhammad; Suhaili, Neviyarni (Counseling and Humanities Review, 2023)
This research is motivated by the large number of student learning outcomes in mathematics that are under the KKM. This happens because there are factors that cause low learning outcomes. Factors causing low student learning outcomes include internal factors consisting of (1) physiological, (2) psychological and external factors consisting of (1) family, (2) school, (3) environment. This research aims to be conducted at SMP Negeri 12 Padang. This research is a quantitative research with descriptive method. The research sample was 234 people. The instrument used is a questionnaire on the factors that cause low student learning outcomes with a Likert scale. The results showed that internal factors consisting of physiological are in the medium category and psychological are in the high category. While external consisting of school factors are in the medium category, family factors, and environmental factors are in the high category.